PEMBERDAYAAN IBU RUMAH TANGGA MELALUI PELATIHAN PEMBUATAN KERIPIK BAYAM DALAM UPAYA PENINGKATAN EKONOMI - Wardany, Kusuma; Sari, Reni Permata; Saputra, Tri Alim; Syaifudin, Rahmat (SWAGATI : Journal of Community Service, 2023)
To foster the creativity of housewives, we, a community service team, intend to hold training on how to make spinach chips by empowering housewives in the Tejosari subdistrict, Metro Timur District. This service activity aims to provide training in processing spinach chips so as to increase economic income for housewives in the Tejosari Village, East Metro District. The methods used are the preparation stage, the implementation stage and the evaluation. The targets and objectives of this community service activity are housewives in the Tejosari Village, East Metro District. This training activity received a positive response from the people of Tejosari Village, East Metro District. The benefits of the activities that have been carried out can be felt directly by the community, especially in activities that can provide additional knowledge for the community or are educational in nature which will greatly influence changes in people's behavior and economic attitudes in everyday life.